International review of neurobiology. - Bradley, Ronald J.; Harris, R. Adron; Jenner, Peter, 1946- (Academic Press, 2001)
Published since 1959, International Review of Neurobiology is a well-known series appealing to neuroscientists, clinicians, psychologists, physiologists, and pharmacologists. Led by an internationally renowned editorial board, this important serial publishes both eclectic volumes made up of timely reviews and thematic volumes that focus on recent progress in a specific area of neurobiology research.